Phytochemical and Anticonvulsant Activity of the Ethanol Root Bark Extract of Mimosa pigra L. (Fabaceae) in Laboratory Animals (Nigerian Journal of Pharmaceutical Research, 2024)
Background and objectives: Various parts of Mimosa pigra (MPG) are used in traditional medicines to treat convulsive disorders. The objective of this study was to investigate the anticonvulsant properties of Mimosa pigra ethanol root extract (EREM).Methods: The acute toxicity of the extract was investigated using OECD 423 protocol of 2002. The anticonvulsant properties of EREM at 200,400 and 800 mg/kg were evaluated using Maximal Electroshock Test (MEST) in chicks; strychnine (SCN-) and pentylenetetrazole (PTZ)-induced seizures in mice.Results: The extract at 400 and 800 mg/kg significantly (p
Keywords: Mimosa pigra; Ethnomedicinal claim; Maximal Electroshock Test; Pentylenetetrazole; Strychnine